2017
DOI: 10.3325/cmj.2017.58.118
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and anti-proliferative action of disintegrin from Echis multisquamatis snake venom

Abstract: AimTo purify the platelet aggregation inhibitor from Echis multisquamatis snake venom (PAIEM) and characterize its effect on platelet aggregation and HeLa cell proliferation.MethodsSodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and matrix assisted laser desorption/ionization time-of-flight (MALDI-TOF) were used for PAIEM identification. Platelet aggregation in the presence of PAIEM was studied on aggregometer Solar-AP2110. The changes of shape and granularity of platelets in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…This was a purified protein validated through SDS-PAGE and LC-MS/MS, and termed purpureomaculin in line with the naming of most snake venom-derived disintegrin protein (prefix "species-" + post-fix "-in"). The finding of purpureomaculin anticancer activity is consistent with earlier studies that reported the inhibitory activity of snake venom disintegrins on the proliferation, metastasis and adhesion of cancer cells [21,25,37]. The selective cytotoxic effect of purpureomaculin in breast cancer cells (MCF7) corroborates the selective cytotoxicity of MTP venom in the same cancer cell line observed in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was a purified protein validated through SDS-PAGE and LC-MS/MS, and termed purpureomaculin in line with the naming of most snake venom-derived disintegrin protein (prefix "species-" + post-fix "-in"). The finding of purpureomaculin anticancer activity is consistent with earlier studies that reported the inhibitory activity of snake venom disintegrins on the proliferation, metastasis and adhesion of cancer cells [21,25,37]. The selective cytotoxic effect of purpureomaculin in breast cancer cells (MCF7) corroborates the selective cytotoxicity of MTP venom in the same cancer cell line observed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The antineoplastic potential of snake venom disintegrins have been shown in several studies, e.g. contortrostatin (disintegrin isolated from Agkistrodon contortrix venom) [23], saxatilin (disintegrin from Gloydius saxatilis venom) [24], PAIEM (disintegrin isolated from Echis multisquamatis venom) [25] and a disintegrin from Crotalus durissus collilineatus venom [26]. The disintegrins act by inhibiting angiogenesis, invasion and migration of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…This method is easy to use and does not require expensive devices. It was successfully used in our laboratory and allowed us to obtain data with high reproducibility [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Concerns over the swift rise in microbial drug resistance have prompted researchers to explore the promising role of snake venom and its components in eradicating superbugs ( Table S1 ) [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In parallel, numerous studies have also been conducted to isolate and characterize peptides found in snake venoms as potential cancer drugs ( Table S2 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Additionally, in recent years, conjugation of s...…”
Section: Introductionmentioning
confidence: 99%